2020
DOI: 10.3168/jds.2019-17446
|View full text |Cite
|
Sign up to set email alerts
|

Feed-derived iodine overrides environmental contribution to cow milk

Abstract: Iodine is deficient in diets worldwide, leading to a range of undesirable health affects at the population level. Dairy products are a primary source of iodine in the diets for those populations in which iodised salt is not systematically utilised or available. Yet, the flows of iodine through dairy agroecosystems are not well understood. The aim of this research was to investigate iodine flows though the dairy agroecosystem; including the influence of atmospheric depositional inputs, environmental variables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Results from this study report soil selenium concentrations are in uenced by soil characteristics and re ect in the grass selenium concentration. Despite the strong environmental relationship, a disconnect in relation to milk selenium concentration and the agricultural land, similar ndings were reported investigating iodine in agronomic environment (McKernan et al 2020). The variable milk selenium concentrations reported in this study is attributable to inconsistent farm management practices where the fodder provided to herds is variable.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Results from this study report soil selenium concentrations are in uenced by soil characteristics and re ect in the grass selenium concentration. Despite the strong environmental relationship, a disconnect in relation to milk selenium concentration and the agricultural land, similar ndings were reported investigating iodine in agronomic environment (McKernan et al 2020). The variable milk selenium concentrations reported in this study is attributable to inconsistent farm management practices where the fodder provided to herds is variable.…”
Section: Discussionsupporting
confidence: 76%
“…Water samples were not collected and analysed in this study, as reported water selenium concentrations are < 10µg/L, subsequently are unlikely to in uence milk selenium concentrations (WHO, 2011). Further details of the sample collection approach have already been reported in McKernan et al, (2020).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With no formal iodine food fortification programme in the UK or ROI, good dietary sources are essential to meet requirements. Food content varies with season and soil content with coastal areas having higher levels [ 21 ]. Dietary habits may change during pregnancy, but it is not known how this affects iodine nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The flow of iodine through agro‐ecosystems including milk, soil, silage, grass and different animal feeds is not well understood 48 . A recent UK report suggested that natural iodine inputs into the environment are dominated by atmospheric deposition, especially sea spray, and so the location of farms relative to the coast and prevailing wind direction is important 49 . The levels of iodine in supplemental feeds were approximately 10‐fold higher than those in forage‐derived feeds and the practice of feed supplementation led to elevated milk iodine 49 …”
Section: Changes In Farming Practicesmentioning
confidence: 99%